Relationship Between Social Support and Coping Strategies and Disease Among the Cancer Patients of the City of Kerman - Soodeh Maghsoodi; Zahra Salehinejad (Gonabad University of Medical Sciences, 2020)
Background: Cancer pain affects coping strategies in patients. Besides, social protection is a tool that helps to alter the patient's encounter with cancer. This study aimed to investigate the relationship between social support, coping, and disease strategies. Methods: This was an analytical cross-sectional study with a quantitative approach, and conducted using a self-made social support questionnaire and the Billings and Mouse coping strategies questionnaire. The study population consisted of all the cancer patients in Kerman City, from September 2016 to March 2017; it was estimated to include 1400 people. Based on the Cochran formula, the study sample size was calculated as 300 cancer patients, which were collected using a systematic sampling method. Also, data analysis was carried out using the Pearson tests and regression in SPSS V. 21.  Results: The results showed a statistically significant association of social support and coping with the disease strategies (P<0.01). Moreover, problem-focused coping has the most positive and direct relationship with social support. Regression analysis also showed that emotional aspects (kindness and shared positive actions), service-practical support, and financial support can predict the coping strategies with disease.  Conclusion: According to the results, it is recommended to formulate a comprehensive care program and increase social support to enhance the problem-focused coping strategies among cancer patients.